Effect of Annealing Temperature on Structure and Magnetic Properties of Zn0.94Mg0.01Mn0.05O Nanoparticles - GÜLER, ADİL; BOYRAZ, CİHAT (SPRINGER, 2019)
Structural and magnetic characteristics of Zn0.94Mg0.01Mn0.05O (ZnMgMnO) nanoparticles synthesized by Sol-Gel preparation technique in a wide temperature range were reported. The influence of annealing temperature on the crystal structure of ZnMgMnO nanoparticles was figured out by X-ray diffraction technique (XRD). To optimize the annealing temperature and reveal the particle formation and size, Scanning Electron Microscope (SEM) imaging technique was performed. The required stoichiometry of the synthesized samples was obtained by an energy dispersive X-ray analysis technique (EDX). Quantum Design Vibrating Sample Magnetometer (QDVSM) tool was used for the magnetic characterizations of Zn0.94Mg0.01Mn0.05O composition. Magnetization measurements as a function of magnetic field (M-H) were performed in the magnetic field up to 10 kOe. Temperature dependence of magnetization measurements (M-T) was taken between 10 and 320 K temperature ranges.
Keywords: ZnMgMnO nanoparticles; Magnetic properties; Sol-gel; Nanostructures; DOPED ZNO NANOPARTICLES; MECHANICAL-PROPERTIES; ROOM-TEMPERATURE; FERROMAGNETISM; ORIGIN